Morphosyntactic characteristics of texts translated from Spanish into Guarani by the participants of the "Linguistic Hackathon" in 2019 (UNIHumanitas, 2024)
This work was carried out with the purpose of describing the morphosyntactic characteristics of the written texts translated from Spanish to Guaraní produced by the participants of the marathon called “linguistic hackathon”, of the year 2019. Regarding the methodology used in this research, the research level was descriptive and with a qualitative approach. We worked with a database of 800 translations -which were made in the hackathon- of which 43 were taken, by a convenience sampling, to be analyzed with the theories of morphology, syntax and translation. It was possible to identify the use of the lexemes and morphemes of Guaraní and its rules, in the results. On the other hand, simple and compound sentences were determined. Finally, the translation procedures were recognized.
Keywords: grammar; morphology; syntax; translation; spanish; guaraní